Proceedings of the Conference on Design and Semantics of Form and Movement (IntechOpen, 2023)
This year we celebrate the 10th edition of the DeSForM conference series. In 2005, DeSForM was born in (Eindhoven) the Netherlands with the premise of creating meaning through objects, interactions and people. Over the years, the DeSForM community has explored and designed objects through a multi-sensorial approach always aiming at enriching users' experiences with them. Throughout previous editions, we have seen the development from digital and mechanical objects that had enriched sensorial presence to adaptive and intelligent objects that feel almost analogous to reality given their increased information processing power and sensory resolution. These are thanks to the recent developments in the material sciences, robotics, information and sensor technology, and improved production techniques. Consider, for example, developments in wearables and embedded or computational materials. Consequently, the arena that belongs to design researchers and practitioners has gotten more sophisticated by being more technical, but also raises new questions regarding the effect and the impact of the new technologically rich designs. In 2017, DeSForM is returning to its place of birth opening up to a broader audience with deeper insights to debate about the future of dynamic 'form' giving and its effects on people and their environment.